Low-dose Bleomycin Injections for Orbital Lymphatic and Lymphatic-Venous Malformations: A Multicentric Case Series Study. Issue 4 (July 2021) - Prat, Daphna; Gomel, Nir; Zloto, Ofira; Anne, Musika; BenSaid, Ahmed; Bhattacharjee, Kasturi; Yassur, Iftach; Sagiv, Oded; Ben Simon, Guy J.
Abstract : Purpose: Orbital lymphatic malformations (LM) are associated with ocular morbidity and facial disfigurement. Surgery is challenging and may not be effective. We describe the outcome of bleomycin injections for venous LM and lymphatic-venous malformation (LVM) malformations of the orbit in 5 tertiary referral centers between January 2010 and December 2018. Methods: Multicenter retrospective case series, 5 oculoplastic referral centers: Sheba and Rabin Medical Centers, Israel; Mulago Hospital, Uganda; Sri Sankaradeva Nethralaya, India; and Clinique Ophtalmologique de Tunis, Tunisia. All patients diagnosed with orbital LM/LVM were assigned to successive (range 1–6) intralesional 5 international units bleomycin injections. They all underwent complete ophthalmic and orbital evaluations, orbital imaging, and ancillary testing as needed. Clinical photographs were assessed pre- and posttreatment along with objective assessments of clinical improvement. Additional injections were provided in cases of incomplete response. Results: A total of 21 patients (17 women, mean ± standard deviation age 18 ± 13 years, range 2–48 years) underwent bleomycin injections. The mean injection dose was 12 ± 10 international units in 1–3 injections. There was a dramatic improvement in lesion size, appearance, proptosis, and ocular motility in 20/21 patients (95%) after a mean follow-up of 18 months. Visual acuity slightly improved after treatment (20/50–20/30; P = 0.076). No side effects were noted after bleomycin injections. Conclusions: Bleomycin injections for LM/LVM of the orbit are effective; local or systemic side effects were not seen in this series. To the best of our knowledge, this is the largest reported series of this treatment. Abstract : Lymphatic and lymphatic-venous orbital malformations are associated with ocular morbidity and facial disfigurement. Surgery is challenging and may not be effective. Bleomycin injections have excellent clinical outcome and high safety profile in nonurgent situations.